Perbandingan Pemikiran Pendidikan Islam K.H. Ahmad Dahlan Dengan K.H. Hasyim Asy’ari - Musliadi Musliadi (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2022)
K.H.  Ahmad Dahlan and KH Hasyim Asy "ari are two big figures who have quite a big influence in Indonesia. Both have also contributed greatly to the development of education in Indonesia, especially natural education. As two figures with different backgrounds and movements  , it will be found that there are differences in Islamic education between the two, in addition to the Schingga similarities in this study, a comparison of the Islamic education of KH Ahmad Dahlan and KH Hasyim Asy "ari. The purpose of this study is to analyze the concept of Islamic education of KH Hasyim Asy" ari and KH. Ahmad Dahlan, then describe the comparative education between Bauepaqtd undnew aveuesiod yeq euempo This research uses a descriptive qualitative approach. Data collection is done by exploring library sources which are carried out in three stages, namely orientation, exploration, and focused research. looking for logical relationships between the thoughts of the characters so that reasons can be found about these thoughts, classifying, generalizing specific ideas.The results showed that (1) KH.  Ahmad Dahlan tried to integrate between religious lessons and general subjects at the same time, so that it was hoped that he could become a "intellectual and intellectual scholar (2) KH Hasyim Asy" ari founded and fostered Islamic boarding schools and also gave general lessons such as mathematics.  geography, Latin, apart from teaching religious science (3) the two shops both have an important role in the development of Islamic education in IndonesiaTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//